Effectiveness of intravenous acetaminophen for postoperative pain management in hip and knee arthroplasties: a population-based study. Issue 5 (13th March 2019) - Stundner, Ottokar; Poeran, Jashvant; Ladenhauf, Hannah Noemi; Berger, Marc Moritz; Levy, Steven B; Zubizarreta, Nicole; Mazumdar, Madhu; Bekeris, Janis; Liu, Jiabin; Galatz, Leesa M; Moucha, Calin S; Memtsoudis, Stavros
Abstract : Background and objectives: The significance of intravenous over oral acetaminophen (APAP) as part of multimodal analgesic protocols is contested, particularly when considering its relatively high price and use in a surgical cohort such as total hip or knee arthroplasty (THA/TKA), which generally tolerates oral medications. This study aims to elucidate APAP's effectiveness in a large, population-based patient sample. Methods: 1 039 647 THA/TKA procedures were sampled from the Premier Healthcare claims database 2011–2016. APAP use was categorized by intravenous/oral and use on the day of surgery, postoperative day 1 and thereafter. Outcomes were opioid utilization (in oral morphine equivalents), length and cost of hospitalization, and opioid-related adverse effects (respiratory, gastrointestinal, and naloxone use as a proxy). Mixed-effects models measured the associations between intravenous/oral APAP use and outcomes. Percent (%) change and 95% CIs are reported. Results: Overall, 23.6% (n=245 454) of patients received intravenous APAP; of these, 56.3% (n=138 180) received just one dose on the day of surgery. After adjustment for relevant covariates, particularly use of >1 dose of intravenous APAP (compared with no use) on postoperative day 1 was associated with −6.0% (CI −7.2% to −4.7%) reduced opioid utilization; this was −10.7% (CI −11.4% to -9.9%) for use of > 1 dose oral APAP on postoperative day 1. Further comparisons regarding other outcomes also favored oral (over intravenous) APAP. Conclusions: These results do not support the routine use of intravenous APAP in patients undergoing lower joint arthroplasty, especially since oral APAP shows more beneficial outcome patterns.